Vertical Temperature Profile of Natural Lightning Return Strokes Derived From Optical Spectra. Issue 8 (26th April 2021) - Boggs, Levi D.; Liu, Ningyu; Nag, Amitabh; Walker, T. Daniel; Christian, Hugh J.; da Silva, Caitano. L.; Austin, Matthew; Aguirre, Fernando; Rassoul, Hamid K.
Abstract: This study reports on spectroscopy results from a high‐speed optical spectrograph of two naturally occurring lightning return strokes. The two strokes occurred near Melbourne, FL and were from two separate flashes that were about 10 min apart and had National Lightning Detection Network (NLDN) peak currents of −19 and −63 kA. The larger peak current stroke was from a dart leader and was the last stroke in a 5 return stroke flash, while the −19 kA stroke originated from a stepped leader and was the only stroke in that flash. From the flash spectra, the return stroke channel temperature was calculated using the neutral lines of 715.7 nm (OI) and 777.4 nm (OI). In addition to the use of the neutral emission lines, the use of novel instrumentation and image processing techniques allowed the temperature to be calculated for nearly the entire visible channel (several km) and for long durations (several hundred μs). This enables temperature estimates on an unprecedented spatial and temporal scale, which show that the vertical temperature profile is not uniform across the channel. The lower altitudes are significantly hotter than higher altitudes near the time of the return stroke, with temperature gradients along the channel as large as 12, 000 K/km. The rate of cooling of the channel is also initially 3–4 times larger at lower altitudes in comparison with the segments at higher altitudes. The stroke with the larger peak current shows larger maximum temperatures, larger temperature gradients along the channel, and also cools quicker. Key Points: Spectra derived temperature estimates for long path lengths (km) of two natural return strokes are presented The peak temperature at lower altitudes is significantly higher, resulting in gradients as a large 12, 000 K/km at return stroke onset As the temperature decays, lower altitudes initially cool faster than higher altitudes for both strokes